2013
DOI: 10.4088/jcp.12m07933
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Satisfaction and Quality of Life in Major Depressive Disorder Before and After Treatment With Citalopram in the STAR*D Study

Abstract: ClinicalTrials.gov identifier: NCT00021528.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Interventions that appear in published original research and/or literature reviews, and are postulated to improve QOL include: cognitive behavioral therapy (28), future-directed therapy (29), combined psychotherapy and pharmacotherapy (30), occupational/vocational therapy (31), dopaminergic agents (32), nutrition and nutritional supplements (33), augmentation with omega-3 (34), exercise (35), meditation and yoga (36), humor (37), massage (38), and music (39). QOL interventions could also include the treatment of possible comorbid medical and psychiatric conditions (40, 41), and treatment of sexual dysfunction (42, 43). However, randomized, controlled, large sample studies need to be conducted to confirm the above interventions’ usefulness in MDD.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions that appear in published original research and/or literature reviews, and are postulated to improve QOL include: cognitive behavioral therapy (28), future-directed therapy (29), combined psychotherapy and pharmacotherapy (30), occupational/vocational therapy (31), dopaminergic agents (32), nutrition and nutritional supplements (33), augmentation with omega-3 (34), exercise (35), meditation and yoga (36), humor (37), massage (38), and music (39). QOL interventions could also include the treatment of possible comorbid medical and psychiatric conditions (40, 41), and treatment of sexual dysfunction (42, 43). However, randomized, controlled, large sample studies need to be conducted to confirm the above interventions’ usefulness in MDD.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual dysfunction is reported to occur in 40–60% of patients with major depressive disorder (MDD), is common in both men and women (Montejo et al, 2019; Montejo, Montejo, & Baldwin, 2018; Perlis et al, 2009; Seidman, 2006), and sexual dysfunction is reported to increase the risk of the development of MDD by 130–210% (Atlantis & Sullivan, 2012; Kennedy & Rizvi, 2009; Saragoussi et al, 2017). In patients with MDD, sexual dysfunction leads to poorer outcomes, and negatively affects medication adherence (Ashton, Jamerson, Weinstein, & Wagoner, 2005; Francois, Levin, Kutscher, & Asemota, 2017; Sansone & Sansone, 2012), which impacts the response to treatment for MDD (Baldessarini & Tondo, 2019), and is associated with impaired quality of life and increased rates of depression relapse (Ishak et al, 2013; Nurnberg, 2008; Saragoussi et al, 2017; Touya, Diamand, Saragoussi, & Francois, 2017; Williams, Edin, Hogue, Fehnel, & Baldwin, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, the types of functional impairments due to MDD vary widely 4. Impairments due to depression affect multiple facets of life, including work productivity,5,6 social functions,7,8 sexual satisfaction,9 life satisfaction,10,11 interpersonal function,12 quality of life,13 and overall health 14. Improvement with antidepressant treatment is not just restricted to change in depression severity 1517.…”
Section: Introductionmentioning
confidence: 99%